A aplicabilidade de conceitos de palavra à língua Noke Koĩ - Falchi, Flávia Leonel (2015)
The Noke Koĩ language, also called by the names Katukina or Vitxináwa in the less recente bibliography, is a Panoan language spoken by the indigenous group Noke Koĩ. This group lives in the Amazon rainforest, in the region of the Juruá river, in two areas, Terra Indígena Campinas/Katukina and Terra Indígena Rio Gregório. Both areas are located in Tarauacá, in the state of Acre, Brazil. This thesis presents an analysis of the application or not to the Noke Koĩ language of the main definitions that there are in Linguistics for the problematic term word. The statement that exists in this field about not being possible to define word likewise for every language is also considered. Therefore, a specific concept for the Noke Koĩ language is formulated, based on the stress and on the number of syllables of the words of this language, in accordance with Aguiar (1994a). According to the analysis realized of the main definitions of word that objectify to be universal, the criterion stress, unsuitable to the Portuguese language (Camara Júnior, 2010, 2011), can be applied to the Noke Koĩ. In this indigenous language, the definition of word based on the writing and the semantic concept can not be used. Possibly a new type of forms, not classified yet by linguistic theory, must be included on the definition formulated by Bloomfield (1926, 1976) and revised by Camara Júnior (1979, 1980, 1996, 2010, 2011).